2015
DOI: 10.1080/15456870.2015.972406
|View full text |Cite
|
Sign up to set email alerts
|

A Postmodern Turn for Social Media Research: Theory and Research Directions for Public Relations Scholarship

Abstract: The public relations literature on social media has focused primarily on how social media platforms can be leveraged to the advantage of organizations for relationship building and so-called dialogue with publics. Yet most research has positioned relationships in social media merely as opportunities for information exchange, perpetuating models of public relations grounded in systems theory that ignore power imbalances. Consequently, this article offers insights from postmodernist theories to first deconstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 50 publications
0
44
0
2
Order By: Relevance
“…This article has shown that those using social media for their own purposes, in this case bloggers, may only want to invite practitioners to be part of the conversation, and take up real estate space on their blog, if a commercial transaction takes place. Kennedy and Sommerfeldt (2015) suggested that social media can give unexpected power to unforgiving parties. The research has shown that bloggers may be 'more forgiving', or at least listen more closely, if money is involved.…”
Section: Discussionmentioning
confidence: 99%
“…This article has shown that those using social media for their own purposes, in this case bloggers, may only want to invite practitioners to be part of the conversation, and take up real estate space on their blog, if a commercial transaction takes place. Kennedy and Sommerfeldt (2015) suggested that social media can give unexpected power to unforgiving parties. The research has shown that bloggers may be 'more forgiving', or at least listen more closely, if money is involved.…”
Section: Discussionmentioning
confidence: 99%
“…The shift towards a transformative image of woman goes along with postmodernism that stresses the significance of understanding power conflicts to analyze social phenomena. Kennedy and Sommerfeldt (2015) explained that postmodernists raised the question of power through looking for "underlying processes of power and discourse that shape social reality and lead us to form consensuses about what we consider "knowledge" while marginalizing voices that disagree with the dominant consensus" (p. 35). To achieve a better understanding of power relationships constructed through social media adverts, the researcher related Cohen-Eliya and Hammer's (2004) concept of transformative and stereotypical images to the semiotics analysis of visual images.…”
Section: Methodology and Theoretical Frameworkmentioning
confidence: 99%
“…Waters, Burnett, Lamm, and Lucas (2009) similarly stressed, "Relationships are the foundation for social networking sites" (p. 102). Kennedy and Sommerfeldt (2015) argued that "scholarship has assumed social media can be used to foster and maintain "relationships," when in actuality such relationships have been articulated in terms of information acquisition and dissemination" (p. 32). This argument stressed the role of social media in establishing a mutual relationship with the target audience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Applying a similar understanding to other areas of social media, such as Twitter, the field of technical communications can be better equipped to offer analytical solutions to potential blunders. PR "scholarship has experienced a gradual transition from a functional perspective to a co-creational one, wherein publics are viewed as co-creators of meaning, not simply as targets or passive recipients of communicative messages, recognizing the meaning-making power of publics in relationships" [11]. As a result, the communicative use of social media implies that there must be a dyadic dialogue, not just a one-way agenda setting or propaganda model style of communication.…”
Section: Literature Review: New Forms Of Audience Analysis Based On Pmentioning
confidence: 99%
“…In the cases of the hashtags #McDStories and #AskJPM, the attempt to co-create an open dialogue between JP Morgan Chase and McDonalds demonstrates a negative response from the public. The negative response is not uncommon, and is identified by Leitch and Neilson that "authentic dialogue is problematic for systems-based PR because it has the potential to produce unpredictable and dangerous outcomes, so organizations may attempt to determine in advance the terms of any public debate in which they engage [13], undermining genuine dialogue" [11]. In both cases-JP Morgan Chase and McDonalds-the immediate organizational response to negative twitter messages was an attempt to end the dialogue, apologize, and miss out on a chance to have a genuine dialogue with their publics.…”
Section: Literature Review: New Forms Of Audience Analysis Based On Pmentioning
confidence: 99%